Knowledge Management and Storytelling as Social Transformation Tools in Educational Tourism on the Citarum River - Delamontano, Eldo; Endyana, Cipta; Winoto, Yunus; Novianti, Evi (Alesha Media Digital, 2025)
Developing sustainable tourism necessitates innovative approaches that integrate environmental conservation, community engagement, and effective knowledge transfer. This study investigates the power of storytelling and knowledge management as catalysts for social transformation within educational tourism along Indonesia's highly polluted Citarum River. Using a mixed-methods approach, the research collected quantitative data from 79 university students via questionnaires assessing their knowledge and perceptions of the Citarum River and sustainable tourism. Qualitative data came from a content analysis of